WE6.5 Back to the future: Does increasing the proportion of local anaesthetic inguinal hernia repairs help achieve a #NetZeroNHS?. (9th August 2022) - Robb, Henry; Gan, Jonathan; Winter-Beatty, Jasmine; Dryden, Simon; Ortega, Patricia; Purkayastha, Sanjay
Abstract: Aim: To investigate whether increasing the proportion of local anaesthetic (LA) inguinal hernia repairs (IHR) provides benefit across the sustainability 'triple bottom line' of environmental, financial, and social improvement. Methods: After establishing suitability criteria for LA IHR, the IHR waiting list was screened and 20 patients were deemed suitable for LA repair. Data was collated on clinical outcomes, surgical timings, medical equipment usage and patient satisfaction. Trust data on our pre-pandemic (2019) practises was analysed to provide environmental and financial estimates. Extensive carbon footprinting was performed of the resources used in LA and general anaesthetic (GA) cases. Results: Of the 20 cases identified, 10 IHRs were performed under LA and 10 under GA. LA IHR had a 53.2% shorter length of stay (LOS) and a 40% reduced complication rate. Analysis of our 2019 data mirrored this with the LA IHR patients having a 4.75-hour shorter LOS. In 2019, only 27.7% of cases were performed under LA, far below that in published literature (Sanjay 2007) of 64%. LA IHR saved 10.2kgCO2e/case. If we increased our annual LA rate to 64%, we would save 2005.12kg/CO2e/year. Financially, our trust would save £15, 984.54/year. Our patient surveys did not identify a difference in quality-of-life outcomes, however our improved clinical outcomes support the superiority of LA IHR for patients. Conclusion: Increasing the number of LA IHRs would provide significant benefits across the triple bottom line. Our carbon emission savings alone is equivalent to driving from London to Edinburgh 12.5 times.